Allogeneic mesenchymal stem cells and xenogenic platelet rich plasma, associated or not, in the repair of bone failures in rabbits with secondary osteoporosis - Rocha,Mariá Andrade de Carvalho (2017)
Abstract Purpose: To assess the efficacy of allogeneic mesenchymal stem cells and xenogenic platelet rich plasma in the treatment of bone failure of osteoporotic rabbits secondary to estrogenic deprivation and iatrogenic hypercortisolism. Methods: Eight female rabbits underwent ovarian resection and corticoid therapy to induce clinical status of osteoporosis. Four failures were produced in the tibiae, with each failure being treated with hemostatic sponge, allogenic mesenchymal stem cells, xenogenic platelet-rich plasma and the association between both. The animals were divided into two groups, evaluated radiographically and histopathologically at 30 and 60 days post treatment. Results: A radiographically confirmed consolidation of bone failures treated with allogeneic mesenchymal stem cells, associated with the histopathological image of mature and immature bone tissue, without evidence of osteopenia, was compared with the other groups, in which radiolucent failures with osteopenia and fibrosis were still present, denoting the satisfactory effect of the first treatment in detriment to the others. Conclusion: The treatment of bone failures of rabbits with secondary osteoporosis with allogeneic mesenchymal stem cells induced greater bone consolidation with mature and immature bone tissue production (p<0.01), when compared to the other treatments.